The Roles of Cytochrome b559 in Assembly and Photoprotection of Photosystem II Revealed by Site-Directed Mutagenesis Studies - Chu, Hsiu-An; Chiu, Yi-Fang (Frontiers in Plant Science, 2016)
Cytochrome b559 (Cyt b559) is one of the essential components of the Photosystem II reaction center (PSII). Despite recent accomplishments in understanding the structure and function of PSII, the exact physiological function of Cyt b559 remains unclear. Cyt b559 is not involved in the primary electron transfer pathway in PSII but may participate in secondary electron transfer pathways that protect PSII against photoinhibition. Site-directed mutagenesis studies combined with spectroscopic and functional analysis have been used to characterize Cyt b559 mutant strains and their mutant PSII complex in higher plants, green algae and cyanobacteria. These integrated studies have provided important in vivo evidence for possible physiological roles of Cyt b559 in the assembly and stability of PSII, protecting PSII against photoinhibition, and modulating photosynthetic light harvesting. This mini-review presents an overview of recent important progress in site-directed mutagenesis studies of Cyt b559 and implications for revealing the physiological functions of Cyt b559 in PSII.